Spatial decision support system for hydrogeological studies in Table Mountain Group Aquifers, Western Cape Province, South Africa - Mlisa, Andiswa (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MA (Geography and Environmental Studies))--University of Stellenbosch, 2007.